An experimental and computational study into the crystallisation propensity of 2nd generation sulflower. Issue 97 (21st November 2019) - Jensen, Torsten T.; Hall, Charlie L.; Potticary, Jason; Andrusenko, Iryna; Gemmi, Mauro; Hall, Simon R.
Abstract : Persulfurated coronene cannot readily nucleate or crystallise due to its preference for face–face over edge–face interactions. Abstract : The crystallisation propensity of the newly synthesised molecule persulfurated coronene has been investigated through a number of experimental methods. Electrostatic potential calculations and multi-molecular optimisations show that face–face interactions are far more favorable than edge–face interactions, severely restricting the ability of the molecule to crystallise.